Estimating radiative impacts of black carbon associated with mixing state in the lower atmosphere over the northern North China Plain. (August 2020) - Hu, Kang; Zhao, Delong; Liu, Dantong; Ding, Shuo; Tian, Ping; Yu, Chenjie; Zhou, Wei; Huang, Mengyu; Ding, Deping
Abstract: Black carbon (BC) exerts important radiative effects over regions with intensive emissions. This study presents in-situ aircraft measurements of BC vertical profiles including mass loading, size distribution and mixing state, spanning a range of pollution levels in both warm and cold seasons over Beijing. The development of planetary boundary layer (PBL) influenced the properties of pollutants at low levels, and regional transport from the southwest elevated the pollution at higher altitudes. Thicker coatings of BC were associated with higher pollution in the PBL, where interactions between BC and other substances intensively took place. Considering the mixing state of BC, the absorption efficiency could be potentially increased by up to 86% and 60% in the PBL and lower free troposphere, respectively. Including a column-integrated absorption enhancement, the in-situ constrained absorption aerosol optical depth at wavelength 870 nm (AAOD870 ) improved the agreement with AERONET by 28%, but the in-situ measurement remained 19% lower. A radiative transfer model finds a BC heating rate of 0.1–0.3 K/d and 0.5–3.1 K/d for less and more polluted environments respectively, and the BC coating effect could positively introduce a +0.1–4.2 Wm -2 radiative forcing. The presence of aerosol layer enhanced the positive vertical gradient of heating rate by redistributing the actinic flux. In particular, this gradient was further enhanced by introducing thickly-coated BC at higher level during the regional transport events, which may promote the temperature inversion and further depress the PBL development on polluted days. Highlights: BC mass loading for less polluted Beijing was consistent with urban EU/NA. BC heating rate in the PBL increased to 0.5-3.1K/d on polluted days and had positive vertical gradient. BC coatings enhanced the columnar absorption up to 80% with positive radiative forcing +0.1–4.2 Wm -2 .